Smoking among dental students at King Saud University: Consumption patterns and risk factors - Abdullah S. AlSwuailem; Majed K. AlShehri; Salwa Al-Sadhan (Elsevier, 2014)
Objective: To assess smoking prevalence among dental students at King Saud University (KSU) and to determine possible risk factors of tobacco use. Methods: A self-addressed invitation letter was sent to all dental students (males and females) at KSU requesting participation in this study. Data on smoking habits, associated risk factors, and demographic factors, such as age, marital status, residency status, the student's year of study, and grade point average, were collected by an electronic self-administered questionnaire sent via email. Data were analyzed using SPSS. Significant differences between different groups were assessed with a Pearson Chi-Square test at α = 0.05. Logistic regression analysis was used to calculate the odds ratio (OR) and 95% confidence interval (95% CI) and to determine the effect of different risk factors on students' smoking habits. Results: Of the 600 registered dental students, 400 students responded (230 males, 170 females), representing a response rate of 67%. More male than female students were current smokers (27.6% vs. 2.4%, p < 0.001). Most smokers used shisha tobacco only (N = 35, 51.5%), followed by both shisha tobacco and cigarettes (N = 17, 25%), or cigarettes only (N = 16, 23.5%). Male students were about 4 times more likely to be smokers if all or most of their friends were smokers compared to students who had some friends who smoked (OR = 3.9, 95% CI = 1.9-7.7). A high proportion of current smokers (47.8%) reported stress as the main reason for smoking. Twenty-six percent of dental students (N = 87) who are currently nonsmokers reported that they have used tobacco at some point in their lives. Over two thirds of sampled students (63%) believed that public tobacco usage is not well addressed in the current college curriculum. Conclusion: Approximately one in every four male dental students at KSU is a smoker. Having friends who are smokers was the most important risk factor associated with smoking. There is a general belief among dental students that public tobacco use is not well addressed in the dental college curriculum. Keywords: Smoking, Tobacco, Dental Student, Shisha, Curriculum